Eco-Friendly Solar Powered Insecticide Spray System for Sustainable Agriculture - Abdul Rahman, Muhammad Shafiq; Mohamad, Khairul Anuar (Evolution in Electrical and Electronic Engineering, 2025)
In this paper, agriculture industry is being developed by various information and advanced communication technologies, such as the Internet of Things (IoT). The rapid implementation of such technologies has remapped almost all other industries and advanced agriculture transforming the industry from statistical to quantitative. Developing solar powered insecticide spray system with internet of things for smart agriculture. It provides green power to the system as it uses solar panels to provide energy to the entire system to maximize results. IoT sensors and devices are installed in the smart farm to capture real-time data on pests and diseases, crop status, as well as environmental data to facilitate efficient and effective insecticide applications. This smart system helps in cutting down the amount of chemicals used and improving the methods of protecting crops through the identification of the affected parts that merit chemical treatment. Solar powered insecticide spray system modifies the use of renewable energy and IoT to improve smart agricultural productivity.